1873 Ga. Code 817-818 - (:unkn) unknown (My University, 1870)
§ 4527: Prohibited the concealed carry of any pistol, dirk, sword in a cane, spear, Bowie knife, or any other kind of knives manufactured and sold for the purpose of offense or defense.
Keywords: CARRY - CONCEALED